Transgenic mouse lines expressing the 3xFLAG‐dCas9 protein for enChIP analysis. (26th February 2018) - Fujita, Toshitsugu; Kitaura, Fusako; Oji, Asami; Tanigawa, Naoki; Yuno, Miyuki; Ikawa, Masahito; Taniuchi, Ichiro; Fujii, Hodaka
Abstract : We developed the engineered DNA‐binding molecule‐mediated chromatin immunoprecipitation (enChIP) technology to isolate specific genomic regions while retaining their molecular interactions. In enChIP, the locus of interest is tagged with an engineered DNA‐binding molecule, such as a modified form of the clustered regularly interspaced short palindromic repeats (CRISPR) system containing a guide RNA (gRNA) and a catalytically inactive form of Cas9 (dCas9). The locus is then affinity‐purified to enable identification of associated molecules. In this study, we generated transgenic mice expressing 3xFLAG‐tagged Streptococcus pyogenes dCas9 (3xFLAG‐dCas9) and retrovirally transduced gRNA into primary CD4 + T cells from these mice for enChIP. Using this approach, we achieved high yields of enChIP at the targeted genomic region. Our novel transgenic mouse lines provide a valuable tool for enChIP analysis in primary mouse cells. Abstract : In this study, we generated transgenic mice expressing 3xFLAG‐tagged Streptococcus pyogenes dCas9 (3xFLAG‐dCas9) and retrovirally transduced gRNA into primary CD4 + T cells from these mice for enChIP. Using this approach, we achieved high yields of enChIP at the targeted genomic region. Our novel transgenic mouse lines provide a valuable tool for enChIP analysis in primary mouse cells.